Pengaruh Waktu Ekstraksi dan Perbandingan Bahan Baku Pewarna Alami Daun Alpukat dan Daun Sirsak - Nabila Aurillia; Tri Widayatno; Agus Haerudin (Pusat riset dan Inovasi Nasional, 2023)
This study explores the use of natural dyes as an environmentally friendly alternative to synthetic dyes for coloring batik fabric. Specifically, the researchers focus on developing natural dyes from a combination of avocado leaves and soursop leaves. The study aims to determine the impact of extraction time and the ratio of avocado and soursop leaves on the color fastness of batik cloth. Experimental methods were employed, with two extraction times (120 and 240 minutes) and three ratios of raw materials (25%:25%, 15%:35%, and 35%:15%) tested. The results of the color fastness test, which assessed washing and rubbing, demonstrated that the mixture of avocado and soursop leaves exhibited good fastness and resistance to rubbing. These findings suggest that the extracted mixture could be used effectively as a natural dye for batik fabric. Overall, this study contributes to the development of eco-friendly alternatives for the dyeing process in batik production.